Teaching intercultural communicative competence through virtual exchange - Monika Hřebačková (Peoples' Friendship University of Russia (RUDN University), 2019)
Due to the current changes in the globalised world and its markets, traditional ways of teaching and learning need to be reconsidered to better equip students with employability skills for their future careers. This paper reflects some of the processes for enhancing multiple literacy practices and transferable skills framed by foreign language courses. In this respect, virtual exchanges create an excellent opportunity to foster these skills. They open space for increasing intercultural awareness, developing communication and collaborative skills, and enhancing information communication technologies. The paper not only gives a selection of motivational practices in teaching intercultural awareness and a foreign language through virtual exchanges but also brings insights into key concepts of intercultural communicative competence and a brief overview of the history of virtual exchange in education. It considers different variables in virtual exchange practice and points out the inevitable changes in the traditional role of a teacher.